Ameliorating Alzheimer’s-like Pathology by Minocycline via Inhibiting Cdk5/p25 Signaling - Zhao, Yu; Wang, Chuanling; He, Wenbo; Cai, Zhiyou (Current Neuropharmacology, 2022)
Background: Minocycline has multiple neuroprotective roles in abundant brain diseases, including the prevention and treatment of Alzheimer’s disease (AD). Cdk5/p25 signaling plays an important role in the onset and development of Alzheimer’s-like pathology. The aim of the present work was to further explore the underlying mechanism which minocycline effects on Cdk5/p25 signaling related to Alzheimer’s-like pathology. Methods: The cognitive function of animals was measured by the Morris water maze test. The levels of Aβ were determined by an enzyme-linked immunosorbent assay. The levels of APP, β- and γ- secretases, and the biomarkers of tau (total tau and hyperphosphorylated tau), inflammatory cytokine and matrix metalloproteinases (MMP-2 and MMP-9), and biomarkers of synapse and Cdk5/p25 signaling, were detected by the Western blotting. The biomarkers of the synapse, inflammatory cytokine, and matrix metalloproteinases (MMP-2 and MMP-9) were also determined by immunofluorescence. Results: Minocycline improved learning and memory in APP/PS1 mice. It limited the production of Aβ and hyperphosphorylation of tau in the hippocampus and ameliorated synaptic deficit. Moreover, it also inhibited the activation of Cdk5/p25 signaling, inflammation, and matrix metalloproteinases. Conclusion: Minocycline mitigates Alzheimer’s-like pathology via limiting the activation of Cdk5/p25 signaling pathway and improves cognitive deficits.
Keywords: cyclin-dependent kinase 5